Perception and use of new technologies in crafts education and craftsmanship among young craftsmen: a study of sustainable practices - Mazur-Włodarczyk, Katarzyna; Rajchel, Anna; Ruszczak, Bogdan (Economics and Environment, 2025)
The research aims to learn the opinions of students enrolled in first- and second-cycle vocational schools in the Opole province (Poland) regarding the utilisation of new technologies in the field of craftsmanship. It covered a number of key issues, including job changes, improvements related to the production and management processes in craft enterprises, activities that accelerate the adoption of new technologies in crafts, and their relationship with sustainable development and building the resilience of craft communities and economies. New technologies in crafts are perceived and applied with a focus on either production or management processes, aiming to either increase profits or promote sustainability and align with either environmental or economic responsibility within the context of sustainable development. During the study, content analysis, linear classification model with L2 regularisation, and verification of the strength of mutual influence using the Spearman rank correlation coefficient were performed. The findings indicate that traditional skills associated with craftsmanship are being transmitted to younger generations, who are growing up in a rapidly evolving technological, social, and economic environment. The application of modern technologies is a crucial factor in the development of crafts and the enhancement of in the market. Vocational education in Poland is in need of reform, and the implementation of modern tools is essential for more effective preparation for the workforce. These technologies facilitate the advancement of production and competitiveness, yet their utilisation must align with the tenets of ecological responsibility.